Spite and virulence in the bacterium Pseudomonas aeruginosa. - Inglis, R; Gardner, A; Cornelis, P; Buckling, A (2009)
Social interactions within populations of pathogenic microbes may play an important role in determining disease virulence. One such ubiquitous interaction is the production of anticompetitor toxins; an example of a spiteful behavior, because it results in direct fitness costs to both the actor and recipient. Following from predictions made by mathematical models, we carried out experiments using the bacterium Pseudomonas aeruginosa to test under what social conditions toxin (bacteriocin) production is favored and how this in turn affects virulence in the larvae of the wax moth Galleria mellonella. Consistent with theory, we found that the growth of bacteriocin producers relative to sensitive non-producers is maximized when toxin producers are at intermediate frequencies in the population. Furthermore, growth rate and virulence in caterpillars was minimized when bacteriocin producers have the greatest relative growth advantage. These results suggest that spiteful interactions may play an important role in the population dynamics and virulence of natural bacterial infections.